Acoustic Emission Experimental Research of the Damage Characteristics of Raw Coal under Different Loading and Unloading Rates - Minbo Zhang; Li Cui; Wenjun Hu; Jinlei Du; Zhen Zhang; Cuiling Wang (Shock and Vibration)
In this study, triaxial load failure experiments of coal samples under different strain rates and different confining pressure unloading rates were carried out using an RTX-1000 rock triaxial apparatus, and the acoustic emission characteristic parameters of a Micro-II acoustic emission imaging acquisition instrument were used to study the acoustic emission characteristics and damage deformation law of coals under different conditions. Damage models were constructed on the basis of the characteristic parameters to analyze the damage law of coal samples. Experimental results show that the acoustic emission (AE) counts and AE energy of the coal samples decrease, but the peak AE counts and peak AE energy increase with the increase in strain rates. The cumulative AE counts decrease from 9902 times to 6899 times, the peak counts increase from 209 times to 431 times, the cumulative AE energy decreases from 6986 aJ to 3786 aJ, and the peak AE energy increases from 129 aJ to 312 aJ. The overall level of the AE count rates and the AE energy of the coal samples decrease, but the peak AE counts and peak AE energy increase with the increase in unloading rates. The cumulative AE counts decrease from 18,689 times to 16,842 times, the peak AE count rates increase from 245 times/s to 535 times/s, the cumulative AE energy decreases from 9846 aJ to 7430 aJ, and the peak energy increases from 257 aJ to 587 aJ. The damage models are constructed on the basis of AE counts, and the comparative experimental and theoretical curves are analyzed to obtain a higher fitness close to 1. The damage threshold increases from 0.30 to 0.50 and from 0.34 to 0.55, and the damage amount increases from 0.50 to 0.60 and from 0.34 to 0.62 with the increase in strain rates and unloading rates. The research results have practical significance for revealing the mechanism of disaster occurrence in actual engineering excavation and proposing engineering measures to prevent coal rock damage and disaster occurrence.